Rapid detection of Aeromonas hydrophila (Chester,1901) infection in freshwater fish by Dot ELISA - Shome, Rajeshwari; Shome, B R; Gaur, K K (Indian Journal of Fisheries, 2011)
The study was undertaken to standardize and evaluate Dot ELISA for the direct detection of A. hydrophila from diseased fish samples and to confirm suspected A. hydrophila cultures isolated from the samples. A total of 58 samples from gill, body mucous and abdominal fluid were collected from 20 infected Indian major carps (C. mrigala-13 and C. catla-7) showing either ulceration accompanied by abdominal dropsy syndrome and degeneration of scales. The recovery of A. hydrophila was highest from the gill samples followed by body mucous and abdominal fluid. In Dot ELISA test, 19 (32.7%) samples were positive out of 58 tested. Further from the 19 Dot ELISA positive swabs, A. hydrophila could be isolated from 15 (78.9%) samples. Similarly out of 40 suspected A. hydrophila cultures tested, 28 (70%) were positive and A. hydrophila was confirmed in 26 (92.8%). The highest number of Dot ELISA positive were found with the cultures isolated from the gill samples (12) followed by 8 each in body mucous and abdominal fluid. The overall sensitivity of the test was found to be 78.9% with tissue samples and 92.8% with suspected A. hydrophila cultures. It is therefore suggested to evaluate and to utilize this test for detection and screening of A. hydrophila infections in fish in field conditions and to confirm the cultures in the laboratory wherever possible.